Application Delivery Order Minimarket Using the Android Gps Tracking facility - Putu Aditya Dharmawan; Erma Suryani (JOINCS (Journal of Informatics, Network, and Computer Science), 2019)
The purpose of this study is a navigation system based on the presence of satellites so that the latitude and longitude coordinates of a place are known. Service to customers at the Basmalah minimarket located in Gedangan, Sidoarjo GPS technology (Global Positioning System) is one of the advanced features available on an android smartphone. still the manual way directly to customers who come to the minimarket. Online ordering and shipping services carried out by couriers will be designed to make it easier for customers and minimarket owners to carry out buying and selling transactions due to limited time and increasing human activity. The minimarket delivery order application using GPS tracking facilities can be accessed using an android-based smartphone as a mobile device. Customers must register first in order to choose the product to be ordered on the item list. The server will receive the order data stored items and request the coordinates of the customer using GPS satellites to provide a navigation path display of the product delivery by the courier to the customer's home so that it will not be misdirected.